Studi Fenomenologi: Peran Operator dalam Penyusunan Laporan Keuangan Berbasis SAKTI - Marlina Irene Hutagalung; Rosidi Rosidi; Lilik Purwanti (Politeknik Ganesha Medan, 2025)
This research aims to provide an in-depth understanding of the meaning of the operator's role in the process of preparing SAKTI-based financial reports. The research method used is descriptive qualitative with a transedental phenomenological approach. Good coordination, technology development, and increased HR competence will work together to improve the efficiency and quality of financial report preparation. This research implies that further research is needed regarding the meaning of the operator's role in other modules in the SAKTI application, in order to see the obstacles that arise in other modules. So that an evaluation can be made to improve the performance of the operators in the future. This research focuses more on the role of operators in producing quality financial reports and seeing how operators interpret their own roles.